2022
DOI: 10.3390/nano12234115
|View full text |Cite
|
Sign up to set email alerts
|

The Antibacterial Properties of Nanocomposites Based on Carbon Nanotubes and Metal Oxides Functionalized with Azithromycin and Ciprofloxacin

Abstract: Different microorganisms are present in nature, some of which are assumed to be hazardous to the human body. It is crucial to control their continuing growth to improve human life. Nanomaterial surface functionalization represents a current topic in continuous evolution that supports the development of new materials with multiple applications in biology, medicine, and the environment. This study focused on the antibacterial activity of different nanocomposites based on functionalized multi-walled carbon nanotu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…Our findings are further supported by, [ 40 ] who investigated nanocomposites consisting of CNTs and metal oxides that were functionalized with azithromycin and ciprofloxacin. They observed that ciprofloxacin‐functionalized nanocomposites exhibited stronger inhibitory capacities against bacterial strains compared to the antibiotic alone.…”
Section: Resultssupporting
confidence: 86%
“…Our findings are further supported by, [ 40 ] who investigated nanocomposites consisting of CNTs and metal oxides that were functionalized with azithromycin and ciprofloxacin. They observed that ciprofloxacin‐functionalized nanocomposites exhibited stronger inhibitory capacities against bacterial strains compared to the antibiotic alone.…”
Section: Resultssupporting
confidence: 86%
“…Carbon-based nanomaterials have unequivocally demonstrated their ability to kill bacteria [ 67 , 68 ]. Among them, CNTs, especially when dispersed in liquid media, have attracted increased attention as antimicrobial nanotools whose efficiency is highly affected by their purity, size distribution, dispersion state, and media [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…[123] The prepared antibiotic-metallic nanoenzymes can undergo a cascade reaction to enhance their antimicrobial effect. [124] The use of natural polyphenol-liganded metal nanoenzymes has shown great potential for delivering metal ions, in addition to stabilizing metal ions through the formation of metal-polyphenol networks, which are rich in phenolic groups. [125] Nevertheless, there are still some challenges associated with the clinical translation of nanoenzymes.…”
Section: Ruthenium-based Nanozymesmentioning
confidence: 99%